Ann Lewis, Anna Vander Goot, Max Schneebeli, Bertha Woodhall, Edward Bradby, and Charlotte Lohrig in Le Lavandou, France - Murrow, Janet Brewster (Tufts Archival Research Center, 2014)
This date is approximate. negatives (photographic). Photograph appears in photo album, MS225.002.00018, p. 016